Analyzing Relationship Between Internal Auditor Capability and Financial Management Quality: A Study at Indonesia Local Governments - Nur Fajri; Irwan Taufiq Ritonga (Universitas Muhammadiyah Malang, 2020)
The purpose of this study is to analyze whether there is relationship between level of local government internal auditor (LGIA) capability and local government financial management (LGFM) quality. Furthermore, this study also identifies factors affecting the presence or the absence of a significant relationship between LGIA capability and LGFM quality. This research uses in-depth interviews and focus group discussion to identify factors affecting the presence or the absence of relationship between LGIA capability and LGFM quality. The results show that there is no relationship between LGIA capability and LGFM quality. The absence of the relationship is caused by dominant role of Local Government Working Units (LGWU) in the process of financial management; improvement of LGIA capability is not followed by improvement on the roles and services provided by LGIA; and potential weakness in assessment process of LGIA capability by The Finance and Development Supervisory Agency. Findings of this study will assist both central and local governments to evaluate “what went wrong” with their Improvement of LGIA Capability Programs and assist central government to formulate a better policy on relationship and coordination among head of local government, LGWU, and LGIA.This research develops a new method to measure LGFM quality comprehensively. This study also fills gap in the literature exploring the relationship between LGIA capability and LGFM quality, which is still rare at present.